Euro‐Atlantic weather regimes and Mediterranean rainfall patterns: present‐day variability and expected changes under CMIP5 projections. (4th November 2013) - Ullmann, A.; Fontaine, B.; Roucou, P.
ABSTRACT Four monthly rainfall patterns (RPs) describing four monthly typical recurrent rainfall spatial features over the Mediterranean area were computed with agglomerative hierarchical clustering: north‐western Mediterranean (NWM), western and south‐western Mediterranean (W&SM), Mediterranean generalized deficit (MGD) and north‐eastern Mediterranean (NEM). The relationship between the monthly frequency of daily weather regimes (WRs) computed for the Euro‐Atlantic region and monthly Mediterranean RPs is analysed over the 1979–2005 period. Overall, the NAO− WR is clearly associated with NWM, the NAO+ with MGD, the Atlantic Ridge (AR) with NAM and the East‐Atlantic with W&SM. Over the 21st century, we find that the winter occurrence of WRs are not significantly modified under future RCP4.5 and RCP8.5 projection. Nevertheless, an eastward shift of the low pressure system during NAO− regimes, an eastward extension of Azores high pressure towards the Mediterranean during NAO+ regimes and an increase in high pressure over the Azores during AR regimes could strengthen the mean relationship between WRs and RPs. These within‐class barometric changes in WRs are mainly observed under the RCP8.5 scenario and in the late 21st century, highlighting their strong dependence on radiative forcing over time.